Increasing Local Salience of Climate Change: The Un-tapped Impact of the Media-science Interface. Issue 6 (18th August 2019) - Howarth, Candice; Anderson, Alison
ABSTRACT: The media play a vital role in framing the narrative on climate change, however little work exists to assess the extent to which local media outlets increase public engagement on climate change through interaction and engagement with local academics. As temperatures rise and concerns mount that we have passed the tipping point, local media play a potentially critical role in communicating how climate change exacerbates their impact. Based on a review of extant literature on this topic, and a small pilot email survey, this article argues that scientists could be more active in increasing local salience of climate change by building trusted relationships with local media. Coverage of science in the media could benefit from closer engagement with local scientists as environmental stories often get more coverage in local media (compared to national media) which constitute an important source of knowledge on climate change. This would enable constructive discussions between local media and scientists, better translation of science to publics, increased awareness and interest of science production locally, and ultimately creating a trusted intermediary in the science-public interface.